The impact of integration of solar farms on the power losses, voltage profile and short circuit level in the distribution system - Abdallah R Alzyoud; Ali S Dalabeeh; Ayman Y. Al-Rawashdeh; Anwar Al-Mofleh; Ahmad Allabadi; Tamadher Almomani; Ayman Hindi (Bulletin of Electrical Engineering and Informatics, 2021)
This paper introduces a study of utilizing solar energy farm that is integrated with the national grid based on intensive data availability of solar energy in Jordan. The study discusses the impact and the ability of integrating solar farms into the national grid of Jordan. The study considerd different cases and, various power system studies for connection points of solar farms to medium voltage networks. Among these studies are short circuit level, voltage profile and power losses. The main objective of the study is to analyze impacts of integration of solar farms on distribution systems of the chosen areas. Photovoltaic (PV) system with varying penetration levels are integrated at different locations (connection points) into the distribution network. Calculations are performed and models are built using actual data obtained from the Jordanian power grid with PV interconnection. The effect of the short circuit level, voltage profile and power losses in the distribution system are also analyzed. Finally, the most suitable method of connecting the solar farm to the national power network is recommended.